The Analysis Effect of Organizational Communication and Self Development Program on Teacher Performance - Esti Susiloningsih; Hendrajaya Hendrajaya; Yulius Luturmas; Muhamad Akbar; Amat Suroso (Journal on Education, 2023)
Determine the relationship between organizational communication, training, and development, and teacher performance is one of the objectives of this study. 58 people totaled as respondents in this study, which used a saturation sample method. The basic data used in this study was collected through giving teachers questionnaires. The analysis approach used in this study, multiple linear regression, is carried out using the SPSS 22 program. The findings of this study suggest that training and development, organizational communication, and teacher effectiveness are all significantly impacted. Teachers' performance is concurrently greatly impacted by organizational communication, training, and growth.